Business, Employment, and Productivity Impacts of Sugar-Sweetened Beverages Taxes - Hattersley, Libby; Fuchs, Alan; Gonima, Alberto; Silver, Lynn; Mandeville, Kate (World Bank, Washington, DC, 2020)
Industry-sponsored studies reporting negative effects of SSB taxes on businesses, employment, and economic growth have been used very effectively to support arguments against SSB taxes and influence health-related policy. These studies tend to be based on questionable assumptions and provide only a partial picture of economic impacts. Emerging evidence from independent evaluation and modelling studies consistently identifies net positive economic impacts from SSB taxes, including overall employment and productivity gains, and increased government spending.